2020
DOI: 10.1101/2020.07.17.20156091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultural values predict national COVID-19 death rates

Abstract: National responses to a pandemic require populations to comply through personal behaviors that occur in a cultural context. Here we show that aggregated cultural values of nations, derived from World Values Survey data, have been at least as important as top-down government actions in predicting the impact of COVID-19. Whereas trust in institutions predicts lower COVID-19 deaths per capita, secular- rationalism and cosmopolitanism each predict more deaths. The effects of these cultural values register more str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This aggregate reduction prevented cases and thereby prevented overall mortality, even if it did not reduce CFR (Figure 2.1). Certain cultural values that show long-standing differences among countries were the most important predictors of a country's ability to mobilize the population en masse to adopt behavioral COVID-19 mitigation measures: These are cultural tightness and cosmopolitanism (Gelfand et al, 2021;Ruck, Borycz, and Bentley, 2021;Ruck et al, 2020). Ultimately, the COVID-19 pandemic ended in a state of global SARS-CoV-2 endemicity: Infection levels were brought into a steady state by population immunity, and that was achieved either through natural infection or vaccination.…”
Section: Engineered Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…This aggregate reduction prevented cases and thereby prevented overall mortality, even if it did not reduce CFR (Figure 2.1). Certain cultural values that show long-standing differences among countries were the most important predictors of a country's ability to mobilize the population en masse to adopt behavioral COVID-19 mitigation measures: These are cultural tightness and cosmopolitanism (Gelfand et al, 2021;Ruck, Borycz, and Bentley, 2021;Ruck et al, 2020). Ultimately, the COVID-19 pandemic ended in a state of global SARS-CoV-2 endemicity: Infection levels were brought into a steady state by population immunity, and that was achieved either through natural infection or vaccination.…”
Section: Engineered Pathogensmentioning
confidence: 99%
“…While China and Russia feature in the scenario of Vignette 2, undeniably, global geopolitical tensions could be very different ten years from this writing. However, such researchers as Gelfand et al (2021) and Ruck, Borycz, and Bentley (2021) have shown that the cultural values that are among the most predictive for pathogen mitigation are multigenerational patterns that are highly resistant to change. Figure 2.2 identifies the countries that we can predictably anticipate will be on the relatively advantaged side of an airborne pathogen pandemic, and these patterns will persist ten and even 20 years from this writing.…”
Section: Vignette 2 Pandemic Geopoliticsmentioning
confidence: 99%
“…The way in which a society responds to a pandemic depends on collective behaviour, which is guided by cultural values specific to the cultural context (Ruck, et al, 2020). National culture is the explanatory vector of cultural differences among societies, and represents the context of collective behaviour.…”
Section: The Impact Of Uncertainty Avoidance During the Covid-19 Crisismentioning
confidence: 99%
“…Uncertainty creates anxiety and insecurity, and the COVID-19 pandemic is considered a more threatening crisis by the people with higher intolerance of uncertainty (Sauer et al, 2020). Thus, the population had to comply with the national rules imposed since the beginning of the COVID-19 crisis; in addition, human behaviours were modelled according to their cultural context (Ruck, et al, 2020).…”
Section: The Impact Of Uncertainty Avoidance During the Covid-19 Crisismentioning
confidence: 99%
See 1 more Smart Citation